The first reported case of Entamoeba infection in a horse in the Federal District - Brito, Michelle Aparecida de Abreu; Alves, Maysa Palazzo; Gomes, Nayara Ayres de Lacerda (Pubvet, 2024)
This study reports the first confirmed case of infection by Entamoeba sp. in an equine in the Federal District (Brazil). An English Thoroughbred equine showed non-specific clinical signs, such as weight loss and behavioral changes. The parasitological examination of the feces revealed the presence of Entamoeba sp., in addition to other helminths. After diagnosis, the animal was treated with moxidectin and praziquantel, resulting in the elimination of the Entamoeba sp. This case demonstrates the importance of parasitological diagnosis in horses, even in those with nonspecific clinical signs. Entamoeba sp. in horses is a rare finding and highlights the need for additional studies to better understand the epidemiology and impact of this parasitic disease on equine health. Furthermore, the case highlights the importance of an accurate diagnosis and adequate treatment to guarantee the health and well-being of animals.